Analysis of Improving Students' Physics Conceptual Understanding through Discovery Learning Models Supported by Multi-representation: Measurement Topic - La Sahara; Nafarudin Nafarudin; Suritno Fayanto; Babajanova Asal Tairjanovna (Indonesian Review of Physics (IRiP), 2020)
This study aimed to analyze students' conceptual understanding by using a multi-representation assisted discovery learning model in measurement. This research was conducted in Public High School 1 Kendari. This research is a quasi-experimental study using a one-group pre-post test design. The research method consisted of a conceptual comprehension test using a caliper and a screw micrometer in an essay in the form of a multi-representational test on long measurements. The analysis showed an increase in conceptual understanding between the pre-test and post-test with an average pre-test score of 16.24 (SD = 14) and a post-test of 61.4 (SD = 21). These results indicate an increase in students' understanding of concepts after learning with an average N-gain increase of 0.5 (SD = 0.2) in the medium category. It also obtained the most significant increase in students' understanding of the indicators mentioned parts caliper and micrometer with an N-gain average of 0.6 in the medium category.